Implementation of The Public Speaking Program in The Training of Speech Skills Among Students at Modern Boarding School Tukung Lumajang for The Year 2020 - Hikmatul Iftitah; Zeiburhanus Saleh (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2022)
This speech Program is an activity that attracts, pleases, and motivates female students to practice speaking skills. As said by Thoriq Muhammad al-Suwaidan, speech is a speech that stretches, where a fluent speaker speaks to a group of people to convince them. The speech Program at the Modern Boarding School Tekung Lumajang in 2020 has a particular goal: female students write the khitobah text before the speech is given. The formulation of the problem of this thesis is how the process of implementing the speech program in training skills in female students at the Modern Boarding School Tekung Lumajang in 2020, the motivating and inhibiting factors of the speech program in training skills in female students at the Modern Boarding School Tekung Lumajang in 2020. The purpose of this thesis is to describe the process of implementing the speech program in training skills in female students at the Modern Boarding School Tekung Lumajang in 2020, to tell the motivating and inhibiting factors of the speech program in training skills in female students at the Modern Boarding School Tekung Lumajang in 2020. Researchers use qualitative research, and the type of research in this study is descriptive. The data collection methods are interview, observation/observation, and documentation. The results of this study showed that the implementation of khitobah activities on female students at Modern Boarding School Tekung Lumajang in training speaking skills is good. Female students use the method of memorizing the text. That is, female students make text then corrected by ustadzah. After the text is fixed, santri memorizes and then displays it. The material in the speech program is all from the Yellow Book. And the media used in speech programs are pulpit and microphone. And as the supporting factors in the speech program are knowing grammar in general (nahwu and sharraf), female students learn Arabic conversation and memorize mufrodat, madrasah diniyyah. And as the inhibiting factors in the speech program are the lack of ustadzah ability in speaking skills, boarding schools do not apply the language environment, the lack of knowledge of female students in vocabulary, and differences in the ability of female students in grammar, lack of time. هذا برنامج الخطابة هي أنشطة جذابة و فرحة و حثة على الطالبات في تدريب مهارة الكلام كما قال طارق محمد السويدان الخطابة في اللغة هي الكلام المنثور، يخاطب به متكلم فصيح جمعا من الناس لإقناعهم. وبرنامج الخطابة بمعهد الخلافية تكونج لوماجانج للسنة 2020 لها الهدف الفريد وهو تكتب الطالبات نسخة الخطابة قبل إلقائها. الأسئلة التي تقدمها الباحثة في هذا البحث العلمي هي كيف تنفيذ برنامج الخطابة في تدريب مهارة الكلام لدى الطالبات بمعهد الخلافية تكونج لوماجانج للسنة 2020م؟، مالعوامل الدافعة والعائقة في تنفيذ برنامج الخطابة في تدريب مهارة الكلام لدى الطالبات بمعهد الخلافية تكونج لوماجانج للسنة 2020م. ويهدف هذا البحث العلمي لوصف تنفيذ برنامج الخطابة في تدريب مهارة الكلام لدى الطالبات بمعهد الخلافية تكونج لوماجانج للسنة 2020م. ولوصف العوامل الدافعة والعائقة في تنفيذ برنامج الخطابة في تدريب مهارة الكلام لدى الطالبات بمعهد الخلافية تكونج لوماجانج للسنة 2020م. استخدمت الباحثة المدخل البحث الكيفي ونوع البحث في هذا بحث هو الوصفي. أما الطريقة التي قدمت الباحثة لجمع البيانات فهي طريقة الملاحظة و طريقة المقابلة و طريقة الوثائقية. ونتائج البحث تدل على أن تنفيذ برنامج الخطابة لدى الطالبات في معهد الخلافية تكونج لوماجانج لتدربات الطالبات في مهارة الكلام قد جيدة. تستخدم الطالبات بطريقة حفظ النسخة وهي تكتب الطالبات النسخة الخطابة وتصحيحها المعلمات ثم يحفظن النسخة قبل إلقاء الخطابة. وأما مواد فهي كل من الكتب السلفية. و أما الوسائل المستخدمة فهي منبر ومكبر الصوت.أما العوامل الدافعة فهي معرفة القواعد العامة (النحوية و الصرفية) و تتعلم طالبات المحادثة وحفظ المفردات و مدرسة الدينية. وأما العوامل العائقة فهي قلة قدرة المعلمات في مهارة الكلام ولا ينفذ معهد البيئة اللغة وقلة قدرة الطالبات في المفردات واختلافة قدرة الطالبات في القواعد وقلة الزمان.